Analysis and mechanical properties characterization of operated gas main elbow with hydrogen assisted large-scale delamination. (December 2017) - Nykyforchyn, H.; Zvirko, O.; Tsyrulnyk, O.; Kret, N.
Abstract: The pipe elbows with hydrogen assisted large-scale delamination revealed in 40-years operated lateral pipelines located behind the compressor station were investigated. The crack on the external surface of the pipe elbow above the delamination was observed. The causes of the material degradation were studied by non-destructive testing using ultrasound thickness meter, microstructure observing, hydrostatic pressure testing, and mechanical properties characterization. The degradation degree of the pipe elbow steel was higher than of the straight pipe steel regardless of a section was tensioned or compressed. Basing on the tensile tests carried out on the cylindrical standard smooth and proposed circular notched specimens it was established that the plasticity of the operated steel could be measured correctly only on the specimens with a notch due to localisation of deformation in the cross section. The limitations in using elongation and reduction in area for characterization of plasticity of the pipe steel with extensive delamination were established. A special short transverse specimen for impact toughness measurement of pipelines steels was designed, fracture plane in which was parallel to the delamination plane. The extremely low KCV values were obtained under designed specimens testing, which correctly characterized brittle fracture resistance of material along structure fibers and a sensitivity of pipe steel to delamination as well. The two stages of in-service degradation of metal, deformation aging and multiple damaging, were analysed, and two substages of the second one were distinguished: dissipated disoriented damaging and damaging oriented in rolling direction. Highlights: Hydrogen assisted large-scale delamination in operated gas main elbow is revealed. In-service degradation degree of the elbow steel is established. Determination of degraded steel plasticity on notched specimens is recommended. A special short transverse specimen for impact toughness measurement is designed. Two substages of the stage of in-service in-bulk metal damaging are distinguished.